Patterns of Patient Flow to Obafemi Awolowo University Teaching Hospital Complex’s Cancer Treatment Centre, Ile-Ife, Osun State, Nigeria - Babatimehin, Oyekanmi; Oladele Olagundoye, Oludotun; Rotimi Afolabi, Matthew (Bulletin of Geography. Socio-economic Series, 2017)
This study analyses the spatial dimensions of patronage of Obafemi Awolowo University Teaching Hospital Complex’s Cancer Treatment Centre, Ile-Ife, Osun State, Nigeria, with a view to provide information on the sphere of influence of the centre and to inform future locational decisions. The geographic coordinates of relevant phenomena were obtained using a GPS receiver. Also, the medical records of cancer patients were assessed for relevant information. The collected data were analysed using descriptive and inferential statistics, and geo-spatial techniques. The data showed that a total of 1809 patients from 15 states in Nigeria were enrolled for the treatment of cancer at the hospital. The volume of patronage at the centre was seen to be inversely related to the distance travelled by patients (r = -.657, p>0.05). For instance, 85% of the patients came from the three (3) states nearest to the health facility, with Osun, the host State, accounting for about half (50.6%) of the total number. Additionally, the study revealed some demographic and socio-economic peculiarities among the cancer patients.